THEORIZING HYBRIDITY: INSTITUTIONAL LOGICS, COMPLEX ORGANIZATIONS, AND ACTOR IDENTITIES: THE CASE OF NONPROFITS. (20th July 2014) - SKELCHER, CHRIS; SMITH, STEVEN RATHGEB
<x xml:space="preserve">Abstract</x> We propose a novel approach to theorizing hybridity in public and nonprofit organizations. The concept of hybridity is widely used to describe organizational responses to changes in governance, but the literature seldom explains how hybrids arise or what forms they take. Transaction cost and organizational design literatures offer some solutions, but lack a theory of agency. We use the institutional logics approach to theorize hybrids as entities that face a plurality of normative frames. Logics provide symbolic and material elements that structure organizational legitimacy and actor identities. Contradictions between institutional logics offer space for them to be elaborated and creatively reconstructed by situated agents. We propose five types of organizational hybridity – segmented, segregated, assimilated, blended, and blocked. Each type is theoretically derived from empirically observed variations in organizational responses to institutional plurality. We develop propositions to show how our approach to hybridity adds value to academic and policy‐maker audiences.